APPLICATION OF THE INDEPENDENT CURRICULUM TOWARDS LEARNING OUTCOMES OF CLASS IV STUDENTS IN MATHEMATICS LESSONS IN PRIMARY SCHOOL 57 BANDA ACEH - Fitria, Husnul; Darnius, Said; Fauzi, Fauzi (Universitas Syiah Kuala, 2023)
The implementation of the Independent Curriculum is one of the ways implemented by the government to improve the quality of education in Indonesia, through the implementation of the Independent Curriculum teachers are expected to be able to improve student learning outcomes on the topic of learning mathematics. Until now the implementation of the Independent Curriculum has not been known to what extent the ability of students in grade IV SD to learn mathematics. The formulation of the research problem is